Organochlorine contamination in sediments collected from a rural-, urban- and industrial-impacted aquatic system (Danube, Serbia) - Brborić, Maja (Array, 2020)
The spatial distribution of various organochlorinated compounds (PCBs and ОCPs (DDTs, HCB, and HCHs)) were investigated in sediments of Serbia's stretch of the Danube River. The obtained concentrations appeared to be relatively low in comparison with other river sediments worldwide. The results demonstrated a wide range of concentrations (µg/kg dry weight) with the following decreasing order: Σ6DDTs (0.70 - 16.65) >Σ 7PCBs (0.25 - 3.54) >Σ 5HCH (0.04 - 2.28) >HCB (0.06 - 0.62), with a dominance of o,p’ -DDT. Relatively higher ΣDDT concentrations and high DDT/DDE + DDD ratios in two sampling locations near the industrial cities indicates a current DDT usage, probably linked to public health concerns. Compositional analyses indicated that hexa- and hepta-PCBs were dominant for PCBs. Our results indicated that the contamination with PCBs came from nonpoint deposition, such as atmospheric contribution and surface runoff, for lightly chlorinated congeners and point source deposition, such as the industrial sources along river flow, for highly chlorinated congeners, whereas OCPs originate mainly from old residues and new usage of pesticides in agriculture and aquaculture. These results contribute to the sparse regional database for organochlorinated compounds in the Danube basin.